Artefactual Skin Disorder: Exploring Clinical Features, Psychiatric Associations, and Contemporary Treatment Approaches: a Narrative Review - Prus, Anna; Zan, Thurein; Urbańska, Julia; Deresz, Franciszek; Narloch, Martyna (Dermatology Review/Przegląd Dermatologiczny, 2025)
Artefactual skin disorder, formerly known as dermatitis artefacta, is a rare psychodermatological condition characterized by self-inflicted skin lesions, the origin of which patients typically deny. This disorder lies at the intersection of dermatology and psychiatry, and as it is often linked to multiple psychiatric comorbidities or psychosocial stressors, it additionally complicates its management. Clinical manifestations vary widely and often mimic other skin conditions, making diagnosis dependent on the exclusion of other diseases and a careful physical examination. Effective treatment includes dermatological care for wound healing, psychotherapy, pharmacological support, and empathetic approach to the patient. This paper aims to outline the clinical features of artefactual skin disorder, describe the latest treatment approaches and underscore the importance of psychiatric and psychological assessment.